The Evolution of Philippine costumes [slides].
Discover the evolution of the baro from its pre-historic roots in the Visayas and of the "Maria Clara" from its humble beginnings as a simple 'patadyong' in the rice fields. Unravel the different modes of fashion that transpired from the 18th to the 20th centuries in the Philippines. Features war costumes during the colonial periods.